2013
DOI: 10.1186/2191-1991-3-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of radiofrequency ablation for patients with varicose veins on the budget of the German statutory health insurance system

Abstract: ObjectivesIn contrast to other countries, surgery still represents the common invasive treatment for varicose veins in Germany. However, radiofrequency ablation, e.g. ClosureFast, becomes more and more popular in other countries due to potential better results and reduced side effects. This treatment option may cause less follow-up costs and is a more convenient procedure for patients, which could justify an introduction in the statutory benefits catalogue. Therefore, we aim at calculating the budget impact of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…19,20 With that, one tends to forget that classic surgery remains the most frequent treatment modality in several countries, such as Spain 18 and Germany. 21 Furthermore, the better outcomes and cost-effectiveness of the endovenous techniques remain debatable. 20,22 In that regard, assessing high ligation and stripping outcomes in the real world remains an important subject and should not be overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 With that, one tends to forget that classic surgery remains the most frequent treatment modality in several countries, such as Spain 18 and Germany. 21 Furthermore, the better outcomes and cost-effectiveness of the endovenous techniques remain debatable. 20,22 In that regard, assessing high ligation and stripping outcomes in the real world remains an important subject and should not be overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…In a work by Kuhlmann and co-workers, varicose vein treatment by HL/S and RFA was modelled in the Statutory German Health Insurance setting. 5 They found that the robustness of the economic analysis deteriorated as the time horizon increased due to the lack of good input data. In light of this potential trade-off between the accuracy of the model and the completeness of the perspective, we believe that this work gives an adequate presentation of the alternative procedures.…”
Section: Discussionmentioning
confidence: 99%
“…A recent example is a German study investigating the impact of reimbursement of a radiofrequency ablation (RFA) procedure for varicose veins. 5 The results of the analysis indicated that a general reimbursement of the procedure through the German Statutory Health Insurance could lead to cost saving for the healthcare sector.…”
Section: Introductionmentioning
confidence: 99%
“…In Germany, the impact of the introduction of Closure Fast™ to the statutory health insurance catalog was assessed. 30 Using a multi-cohort Markov model, which looks at the number of procedures a patient needs to remain free of the symptoms of varicose veins over 5 years, the introduction of Closure Fast™ would save €19.1 million when compared with open surgery. If Closure Fast™ was not used, of the estimated 1.6 million procedures done over 5 years, 38% would have required an inpatient stay.…”
Section: Findings From Literature Searchmentioning
confidence: 99%